Menelisik Kewajiban Suami: Membuka Tanggung Jawab Keluarga Menurut Kitab-Kitab Klasik - Kurniasih, Dwi (SHAHIH: Journal of Islamicate Multidisciplinary, 2020)
This article aims to explain the husband's obligation to his wife from the point of view of classical books and Islamic literature. Household activities which include cooking, washing and caring for children are considered a woman's obligation. The stereotype that emerged in the community was that a woman who was a wife had to prepare all the needs of her husband including cooking, washing, and caring for children. The method used in writing this article is a descriptive qualitative method with a literature study approach, namely studying Islamic literature. The results of this study indicate that based on the results of the classic books, husbands are obliged to provide physical and spiritual support for their wives, including cooking and washing because it includes birth. While the obligation of a wife is pleasing and obedient to her husband.